Thinking about hallucinations: why philosophy matters. Issue 2 (4th May 2022) - Wilkinson, Sam; Green, Huw; Hare, Stephanie; Houlders, Joseph; Humpston, Clara; Alderson-Day, Benjamin
ABSTRACT: Introduction: Hallucinations research is increasingly incorporating philosophy or the work of philosophically trained individuals. We present three different ways in which this is successfully implemented to the enhancement of knowledge and understanding of hallucinations and related phenomena. Method: We review contributions from phenomenology, philosophy of cognitive science, and philosophy of science and psychiatry. Results: We demonstrate that these areas of philosophy make significant contributions to hallucinations research. Phenomenology gives us a sophisticated and critical understanding of the lived experience of hallucinations. Philosophy of cognitive science enables big-picture theorising and synthesis of ideas, as well as a critical engagement with new paradigms. Philosophy of science and psychiatry raises valuable and theoretically informed questions about diagnosis and categorisation. Conclusions: These contributions reflect both the methodological variety within philosophy and its relevance to the hallucinations researcher.